2020
DOI: 10.1177/2309499020918402
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative lymphocyte percentage and neutrophil–lymphocyte ratio are useful markers for the early prediction of surgical site infection in spinal decompression surgery

Abstract: Purpose: Although the neutrophil–lymphocyte ratio (NLR) is a simple biomarker for inflammation, its diagnostic value for predicting surgical site infection (SSI) after spinal decompression surgery has not been extensively investigated. We aimed to determine the predictive value of NLR for SSI in patients undergoing spinal decompression surgery. Methods: We performed a retrospective observational study of patients who underwent spinal decompression surgery. Consecutive 254 patients were divided into an SSI grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
2
18
1
1
Order By: Relevance
“…Thus, increased NLR is considered a possible sign of contamination 24,25 . Indeed, similar to our findings, the increase in NLR detected after some surgical operations have been reported as a useful marker for detecting postoperative infections 26,27 . These factors are similar to and suggestive of the possible factors previously reported.…”
Section: Resultssupporting
confidence: 91%
“…Thus, increased NLR is considered a possible sign of contamination 24,25 . Indeed, similar to our findings, the increase in NLR detected after some surgical operations have been reported as a useful marker for detecting postoperative infections 26,27 . These factors are similar to and suggestive of the possible factors previously reported.…”
Section: Resultssupporting
confidence: 91%
“…In this study, the small increase in NLR in laparoscopic surgery compared to open surgery is thought to be due to minimal incision and surgical manipulation, and this is associated with rapid recovery, low incidence of surgical site infections, and short hospital stay [ 27 , 28 , 29 ]. These results are consistent with a study that reported that laparoscopic surgery had less postoperative inflammatory responses than open surgery [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 - 23 Furthermore, it has been actively reported recently that the percentage of lymphocyte to total WBC count or the ratio of lymphocyte to neutrophils indicate latent infection. 24 - 26 We therefore defined the latent infection as those satisfying either cases with lymphocyte count <1000/μL or cases comprising <10% of the total WBC count around postoperative day 4, and investigated how many such latent infection cases existed and whether any change in the proportion of such cases occurred with the approach change; that is, whether the latent infection rate changed. Specifically, postoperative white blood cell count and postoperative lymphocyte count were measured and compared before and after the change in approach.…”
Section: Methodsmentioning
confidence: 99%